The relation between serum lipids and lutein and zeaxanthin in the serum and retina: results from cross-sectional, case-control and case study designs - Renzi Lisa M; Hammond Billy R; Dengler Melissa; Roberts Richard (Lipids in Health and Disease, 2012)
Abstract Background The xanthophyll carotenoids lutein (L) and zeaxanthin (Z) are found in and around the macula of the primate retina, where they are termed macular pigment (MP). Dietary L and Z are absorbed with fat in the gut and transported on lipoproteins to the retina. Both MP and serum lipoproteins have been related to risk for neurodegenerative diseases such as age-related macular degeneration (AMD). L and Z are carried on both HDL (related to reduced risk of AMD) and LDL (related to increased risk). The purpose of this set of studies was to analyze the relation between L and Z in the serum and retina with the circulating lipid profile. Methods In all experiments, lipoproteins were measured enzymatically from plasma, and MP optical density (MPOD) was measured using customized heterochromatic flicker photometry. Experiment 1: Relations between serum L and Z, MPOD and lipoprotein levels. 108 young, healthy subjects (M = 23.2, SD = 4.12 years) participated. Lipoprotein levels and MPOD were measured. In a subset of 66 participants, serum L and Z levels were also measured using high-performance liquid chromatography. Experiment 2: Relations between lipoprotein levels and MPOD in statin users. 20 subjects (M = 58.05, SD = 11.08 years) taking statin medication and 20 subjects (M = 57.95, SD = 11.03 years) not taking satin were recruited for participation. MPOD and lipoprotein levels were measured. Experiment 3: lowering lipoprotein levels to impact MPOD. One individual (aged 41 years) with high MP density adhered first to an atorvastatin regimen, then, after a wash-out period, to a rosuvastatin regimen. Results Experiment 1: HDL were significantly (p < 0.05) related to MPOD (r = 0.33), to serum L (r = 0.36) and to serum Z (r = 0.26). MPOD was also significantly related to total cholesterol (r = 0.19). Experiment 2: MPOD was not lower in statin users when compared to matched non-statin users, but MPOD decreased significantly with increased duration of statin use (r = −0.63). Experiment 3: Administration of a statin regimen reduced MPOD with atorvastatin (p < 0.05) but not with rosuvastatin. Conclusions Serum xanthophylls, retinal xanthophylls and lipoprotein concentrations are significantly related, and changing lipoprotein levels may impact levels of retinal xanthophylls.